If f(x) = 3x + 2 and g(x) = x^2+ 1, which expression is equivalent to (fºg)(x)?​

Question

If f(x) = 3x + 2 and g(x) = x^2+ 1, which expression is equivalent to (fºg)(x)?​

in progress 0
Arianna 3 months 2022-02-06T18:54:04+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-02-06T18:56:00+00:00

    Answer:

    3x^2+5

    Step-by-step explanation:

    f(x) = 3x + 2 ; g(x) = x^2+ 1

    (fºg)(x) = 3(x^2+ 1)+2

    (fºg)(x) = 3x^2+3+2

    (fºg)(x) = 3x^2+5

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )